Enriching Grammatical Understanding of Using Japanese Part of Speech in Dokkai Learning with the AI-Powered Oyomi Application - Mahira, Nisrina Ishmah; Pratiwi, Iswi Nur; Putri, Evlyn Jane; Yanti, Sevia Dwi; Afifah, Najla Putri; Hidayat, Daffala Viro; Ramadhan, Husni Mubarok; Lestari, Humannisa Rubina (Indonesian Journal Publisher, 2024)
This research focuses on the impact of the Oyomi application on the comprehension of Japanese word classes (part of speech) and sentence structures. The primary issue addressed is the need for efficient and effective language learning tools. The objective is to explore the role of artificial intelligence (AI) within the application in enhancing Dokkai learning. The methodology encompasses a comprehensive analysis of the two principal features contributing to Dokkai learning, the utilization of AI technologies, and a comparison between traditional learning vs AI-powered mobile learning methods. Data collection involved simple linear regression statistical analysis using an F-test and correlation coefficient to gauge the relationship between the usage of the AI-powered Oyomi application and the comprehension of word classes in Dokkai learning. The F test results of 0.01 < 0.05 indicate a significant contribution and a correlation coefficient of 0.8 means the strength of the relationship is very strong. These findings show that AI, when integrated into language learning applications like Oyomi, can provide a more efficient and effective learning experience, especially in Japanese reading comprehension.